(untitled) (Hekima Review, 1992)
To write on the theme of magisterium in the Johannine Writings would have doubtlessly been considered a folly by scripture scholars twenty years ago. The individual believer seems to be much more important to the authors of the Johannine Writings than the church with its structures and teachings office.